Green IS for Sustainable Decision Making in Software Management - Anthony, Bokolo Jnr.; Mazlina, Abdul Majid (Penerbit UTM Press, 2016)
Software industries, society and government are becoming increasingly concerned about the impact of the increasing use of IT infrastructure on the environment, especially in terms of energy efficiency, emission reduction and toxic waste. There are few models or frameworks that can assist software practitioners in making decision on how to integrate sustainable green practices in software management process. Thus this paper contributes and studies on the use of information systems to support sustainability in software industries known as “Green IS” and provides a preliminary insight into the utilization and integration of sustainability in software management process as well as the variables that influence eco-environmental practices by proposing a model that will assist decision making for sustainable software management process. Thus contributions of Green Information Systems (IS) to the objectives of software management process are examined by exploring secondary data from literature. Findings from this paper show how the proposed model contributes to sustainable software management process. The proposed model provides software developer, software managers, and other software practitioners with new insights and enables a more systematic application of sustainable practices in software processes.